Assessment of TP53 mutations in benign and malignant salivary gland neoplasms. - Carolina Cavaliéri Gomes (Public Library of Science (PLoS), 2012)
Despite advances in the understanding of the pathogenesis of salivary gland neoplasms (SGN), the molecular pathways associated with enhanced tumor growth and cell survival remain to be established. The aim of the present study was to investigate whether TP53 mutations are relevant to SGN pathogenesis and if they impact on p53 protein expression. The study included 18 benign and 18 malignant SGN samples. Two polymorphic microsatellite markers at the TP53 genetic locus were chosen to assess loss of heterozygosity (LOH) in the samples that had matched normal DNA. The TP53 exons 2-11 were amplified by PCR, and all of the products were sequenced. Reverse transcription-PCR of the TP53 open reading frame (ORF) was carried out in the samples that had fresh tissue available, and immunohistochemistry for the p53 protein was performed in all samples. TP53 LOH was only found in two pleomorphic adenomas. We found two missense mutations in exon 7 (one in a pleomorphic adenoma and the other in a polymorphous low grade adenocarcinoma), another in exon 8 (in a carcinoma ex pleomorphic adenoma) and a fourth missense mutation in exon 10 (in a mucoepidermoid carcinoma). In addition, a nonsense mutation was found in exon 8 of an adenoid cystic carcinoma. Several intronic and exonic SNPs were detected. Although almost all of the malignant samples were immunopositive for p53, approximately 37% of the benign samples were positive, including the sample harboring the missense mutation and one of the samples that showed LOH. The complete TP53 ORF could be amplified in all samples analyzed, including the IHC negative samples, the samples showing LOH and one sample displaying a missense mutation. In summary, our results show that TP53 mutations are not a frequent event in SGN and that p53 immunopositivity might not be associated with sequence mutations in SGN.